Shear Wave Velocity of the Antarctic Upper Mantle from Full Waveform Inversion and Long Period Ambient Seismic Noise - Emry, Erica (IEDA: US Antarctic Program Data Center, 2023)
This dataset provides the shear wave velocity model resulting from a full-waveform inversion that was constrained using long-period empirical Green's functions extracted from ambient seismic noise. These results were presented by Emry and Hansen at the 2022 Fall Meeting of the American Geophysical Union.